Global imbalances: Is Germany the new China? A skeptical view - Joshua Aizenman; Rajeswari Sengupta (University of California, Economics Department, 2010)
In this paper we evaluate the current account patterns of China and Germany. We point out that China's current account surplus as a share of global GDP in recent years resembles that of Germany's. Yet, an important difference is that the Euro block's current account inclusive of Germany, has overall been balanced, whereas emerging Asia's current account inclusive of China, has mostly been characterized by sizable surpluses. We further find that both China and Germany's current account surpluses seem to be accounted for by common factors. However we have reasons to doubt the long run viability of these current account trends in future decades. Demographic transitions in China and Germany are projected to reduce their surpluses, and this effect is stronger for Germany. We also discuss plausible reasons to doubt the extent to which the Euro block will move towards significant surplus in the coming years.
Keywords: F15; F32; 330; current accounts; demographic transitions; global imbalances; Zahlungsbilanzungleichgewicht; Leistungsbilanz; Vergleich; Deutschland; China